The Influence of Eggshell Particle Sizes on the Adsorption of Organic Dye - Fahad, Besma Mohammed; Ali, Nisreen Sabah; Hameed, Tamarah T. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
This work aimed to use effective, low-cost, available, and natural adsorbents like eggshells for removal of hazardous organic dye result from widely number of industries and study the influence of different eggshell particle size (75, 150) Mm. The adsorbent was characterized by SEM, EDX, BET and FTIR . The initial pH of dye solutions varying from 4 to 10 , the initial concentrations of methyl violet (MV) 2B range (20-80) mg/L, dosage range (0.5-10) g, contact time (30-180) min, and particles size of the adsorbent (75, 150) Mm were selected to be studied. Two adsorption isotherms models have been used to fit the experimental data. Langmuir and Freunlich models were found to more represent the experiments with high correlation coefficient. The results showed that the variation in particle size of eggshells powder statistically has slight effect on the removal of (MV). The highly percentage of dye removal (97.27%) by using eggshells was observed with particle size of 75Mm, pH 4, at room temperatures for 30 min, 10 g adsorbent dose and 20 mg/L initial dye concentration.